THE DIALECTIC OF ARISTOTLE’S TOPICS - Szynwelski, Cristiane (2022)
This article contains an outline of the dialectic of Aristotle's Topics and explanations of some passages in the work, as a propaedeutic for its reading. The first section contains a summary of the problem of the definition of the Aristotelian dialectic and explains that its solution demands a research beyond the Topics. The second and third sections show what is possible to know about dialectic from the study of this work: a technique of reasoning as it is applied to academic training and also, to some extent, to the dialectical disputes of ancient Greece. The article also draws attention to several details and differences regarding the contextualization of Topics passages, which serve to prevent misinterpretation.